Peran Ekstrakurikuler dalam Membentuk Karakter Siswa - Eli Masnawati; Didit Darmawan; Masfufah Masfufah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Extracurricular activities are an integral part of school education that focuses on academics, and plays a role in character building. These activities outside of the main curriculum provide opportunities for students to develop a range of skills and positive values that can enhance their academic performance, and form a strong personality and character. Extracurricular activities provide a platform for the development of social skills, leadership, teamwork, and self-responsibility. This is a descriptive qualitative research. The study used an interactive model to analyse the research data. Thus, it can be concluded that extracurricular activities are not just additional activities outside of class hours, but they play an invaluable role in student character building. Through the various activities offered, extracurricular activities are able to open the door to self-discovery, skill development, and strengthening of positive values. Active involvement in extracurricular activities enriches students' experiences, and contributes greatly to forming a person who is resilient, has integrity, and is ready to face the challenges of life.